1990
DOI: 10.1084/jem.172.6.1741
|View full text |Cite
|
Sign up to set email alerts
|

Endothelins, peptides with potent vasoactive properties, are produced by human macrophages.

Abstract: SummaryEndothelins are peptides, originally isolated from endothelial cells, with potent vasoactive and mitogenic properties. In this study, we demonstrate that human macrophages synthesize and secrete endothelins . Cultured human macrophages were found by immunocytochemistry to stain positively for endothelin 1 and endothelin 3. Their capability to produce and release these peptides was confirmed by a combination of reverse-phase high-performance liquid chromatography and radioimmunoassays, specific for endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
196
0
10

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(213 citation statements)
references
References 20 publications
7
196
0
10
Order By: Relevance
“…It is therefore likely that the high levels of ET-1 detected in P. aeruginosa-infected patients genuinely reflects an up-regulation of ET-1 expression by P. aeruginosa infection. Other bacterial products such as Escherichia coli lipolysaccharide and pro-inflammatory cytokines, such as IL-1b and TNFa also up-regulate ET-1 expression in human bronchial epithelium [6]. Migration of neutrophils from the intravascular compartment to an inflammed tissue requires interaction of neutrophils with vascular endothelium and the presence of chemoattractants which serve as homing triggers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore likely that the high levels of ET-1 detected in P. aeruginosa-infected patients genuinely reflects an up-regulation of ET-1 expression by P. aeruginosa infection. Other bacterial products such as Escherichia coli lipolysaccharide and pro-inflammatory cytokines, such as IL-1b and TNFa also up-regulate ET-1 expression in human bronchial epithelium [6]. Migration of neutrophils from the intravascular compartment to an inflammed tissue requires interaction of neutrophils with vascular endothelium and the presence of chemoattractants which serve as homing triggers.…”
Section: Discussionmentioning
confidence: 99%
“…2). Sputum leukocyte density was higher in P. aeruginosa-infected (median 48.7, interquartile range 15.7±97.7310 6 . mL -1 ) than in non-P. aeruginosa-infected patients (9.1, 1.5±25.5310 6 .…”
Section: Patient Demographic Data and Clinical Characteristicsmentioning
confidence: 93%
“…The ability of human macrophages to secrete ET,.1 has been recently documented [8]. This publication has reported that PMA.…”
Section: November 199mentioning
confidence: 92%
“…At the end of the attachment period the medium was rcplaccd with MEM supplcmcntcd with IO% FCS for the rest of the cxperimcnts. Cells were used hc!wccn day 15 and 20 after seeding [8]. For each cxpcriment (rr=3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation